Beyond listening: the distinct effects of proactive versus responsive customer orientation on the reduction of uncertainties at the fuzzy front end of innovation. (30th November 2016) - Schweitzer, Fiona; Palmié, Maximilian; Gassmann, Oliver
Abstract : The extent to which the intensity of R&D employees' interaction with market‐oriented employees, proactive customer orientation, and responsive customer orientation affect the ability to reduce product‐related uncertainties at the fuzzy front end of innovation was analyzed. They investigated 160 product innovation projects in various high‐tech industries and identified proactive customer orientation as an important moderator of the link between R&D employees' interaction with market‐oriented employees and the reduction of product‐related uncertainties at the fuzzy front end. They also found that responsive customer orientation diminishes the ability to reduce product‐related uncertainties at the fuzzy front end. The theoretical and managerial implications of the results are discussed.